Xpert® bladder cancer detection as a diagnostic tool in upper urinary tract urothelial carcinoma: preliminary results. (April 2022) - D'Elia, Carolina; Trenti, Emanuela; Krause, Philipp; Pycha, Alexander; Mian, Christine; Schwienbacher, Christine; Hanspeter, Esther; Kafka, Mona; Palermo, Margherita; Spedicato, Giorgio Alfredo; Holl, Stefanie; Pycha, Armin
Objectives: Upper urinary tract urothelial carcinoma (UTUC) represents about 5–10% of all urothelial malignancies with an increasing incidence. The standard diagnostic tools for the detection of UTUC are cytology, computed tomography (CT) urography, and ureterorenoscopy (URS). No biomarker to be included in the daily clinical practice has yet been identified. The aim of our study was to evaluate the potential role of Xpert® Bladder-Cancer (BC)-Detection in the diagnosis of UTUC. Methods: Eighty-two patients underwent 111 URS with Xpert® BC-Detection, cytology, or Urovysion® analysis of UT for suspicion of UTUC. Twenty-four cases were excluded from the analysis due to a non-diagnostic Xpert® BC-Detection, cytology, or Urovysion®. Samples were analyzed with upper tract (UT) urinary cytology, with Xpert® BC-Detection on UT urines, and with Urovysion® Fluorescence in situ hybridization (FISH) test. After urine collection, the patients underwent retrograde pyelography and/or URS, and if positive a UT biopsy. The Xpert® BC-Detection was reported by the software as negative or positive [cut-off total Linear Discriminant Analysis (LDA) = 0.45]. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of cytology, Xpert® BC-Detection and Urovysion-FISH were calculated using URS and/or histology results as reference. Results: In all, 27 (31%) of 87 URS resulted positive, with 20 low-grade (LG) and 7 high-grade (HG) tumors. Overall sensitivity was 51.9% for cytology, 100% for Xpert® BC-Detection, and 92.6% for Urovysion. The sensitivity of cytology increased from 26% in LG to 100% in HG tumors. For Xpert® BC-Detection, sensitivity was 100% both in LG and in HG, and for Urovysion-FISH, it increased from 90% in LG to 100% in HG tumors. PPV was 82.4% for cytology, 35% for Xpert® BC-Detection, and 73.5% for Urovysion. NPV was 81.4% for cytology, 100% for Xpert® BC-Detection, and 96.2% for Urovysion. Conclusion: The excellent NPV of Xpert® BC-Detection allows to avoid unnecessary endoscopic exploration of the UT, reducing invasiveness and URS complications in the follow-up of UTUC.